Peran Kolaborasi dan Persaingan Bisnis dalam meningkatkan Kinerja Usaha di Era Industri 4.0 pada Pedagang Mie Ayam dan Bakso Di Kota Sukabumi - Aqli, Aldi; Noor Rachmah, Yulia; Anggraeni Hidayat, Wina (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to examine the role of collaboration and business competition in improving the business performance of chicken noodle and meatball vendors in Sukabumi City during the Industry 4.0 era. A qualitative case study approach was employed, involving vendors and customers as key informants. The findings indicate that collaboration among vendors—such as joint procurement of raw materials, co-promotions, and shared delivery services—helps reduce operational costs and expand market reach. Meanwhile, healthy business competition encourages innovation in product offerings, pricing, service quality, and digital technology adoption. Cross-sector collaborations with government bodies, academia, and local communities further strengthen the competitiveness of small culinary businesses amidst a rapidly evolving digital market. Thus, the synergy between collaboration and competition is a crucial factor in enhancing performance and sustaining traditional culinary businesses in the age of industrial transformation.